Diseño, construcción y validación de un instrumento para evaluar el riesgo psicolaboral en empresas colombianas (2008)
The purpose of the study was to design, construct and validate a Psychosocial Risk Measure (IMP) Instrument. The IMP is conformed by 52 items which evaluate the psychosocial risk through seven dimensions: job loads, role definition, task identification, job level responsibility, management characteristics, social group of work characteristics and organizational characteristics. Five phases was carried out: a) theoretical and conceptual boarding of the psychosocial risk; b) test design; c) judges evaluation; d) instrument implementation; and e) results analysis and discussion. IMP was applied to 442 workers, from seven companies, some private and some public, in Bogotá. Reliability coefficient of Cronbach's Alpha was 0.843. Key words: psychosocial risk, occupational health, validation, organization.